Quantitative assessment of the choroidal vasculature in myopic macular degeneration with optical coherence tomographic angiography - Dan, Yee Shan; Cheong, Kai Xiong; Lim, Shen Yi; Wong, Qiu Ying; Chong, Rachel S.; Wong, Chee Wai; Hoang, Quan V. (Frontiers in Ophthalmology, 2023)
Background To assess and compare choroidal morphometric vascular parameters, using optical coherence tomographic angiography (OCTA), in highly myopic adults with and without myopic macular degeneration (MMD). Methods This is a clinic-based observational study of 148 eyes with axial length (AL) ≥25mm, enrolled from the high myopia clinic of the Singapore National Eye Centre. MMD was graded from fundus photographs. Swept source OCT (SS-OCT) and OCTA were performed and assessed for choroidal layer thickness (CT) and choroidal vasculature (choroidal vessel density (CVD), choroidal branch area (CBA) and mean choroidal vessel width (MCVW)) in the different choroidal layers (overall choroidal layer (CL), medium-vessel choroidal layer (MVCL), large-vessel choroidal layer (LVCL)). Results CTCL (r=-0.58, p<0.001), CTMVCL (r=-0.22, p=0.04), MCVWCL (r=-0.58, p<0.001), and CVDCL (r=-0.19, p=0.02) were negatively correlated with AL, while CBACL (r=0.61, p<0.001) was positively correlated. Compared to eyes with no MMD, eyes with MMD2 had lower CTCL (120.37±47.18µm vs 218.33±92.70µm, p<0.001), CTMVCL (70.57±15.28µm vs 85.32±23.71µm, p=0.04), CTLVCL (101.65±25.36µm vs 154.55±68.41µm, p=0.001) and greater CVDCL (71.10±3.97% vs 66.97±3.63%, p<0.001), CVDMVCL (66.96±2.35% vs 65.06±2.69%, p=0.002), CVDLVCL (68.36±2.56% vs 66.58±2.88%, p=0.012), MCVWMVCL (6.14±0.34µm vs 5.90±0.35µm, p=0.007), and CBACL (12.69±1.38% vs 11.34±1.18%, p<0.001). After adjusting for age, thicker CTCL (odds ratio (OR) 0.98, 95% confidence interval (CI) 0.97-0.99, p<0.001), CTMVCL (OR 0.97 (0.94-0.99), p=0.002) and CTLVCL (OR 0.97 (0.96-0.98, p<0.001) were significantly associated with lower odds of MMD2, while increased CVDCL (OR 1.37 (1.20-1.55), p<0.001), CVDMVCL (OR 1.39 (1.12-1.73), p=0.003), CVDLVCL (OR 1.31 (1.07-1.60), p=0.009), CBACL (OR 2.19 (1.55-3.08), p<0.001) and MCVWMVCL (OR 6.97 (1.59-30.51), p=0.01) was significantly associated with higher odds of MMD2. Conclusion Decrease in choroidal vessel width, density and thickness, and an increase in vascular branching were observed in eyes with long AL. A thinner and denser choroid with greater branching area and vessel width, which may all be signs of hypoxia, were associated with greater odds of MMD2.